Novel ß-HPV49 transgenic mouse model of upper digestive tract cancer - Viarisio, Daniele; Flechtenmacher, Christa (Cancer research, 2016)
The beta genus of human papillomaviruses (ß-HPV) includes approximately 50 different viral types that are subdivided into five species (ß-1 through ß-5). Nonmelanoma cancers may involve some ß-1 and ß-2 HPV types, but the biology of most ß-HPV types and their possible connections to human disease are still little characterized. In this study, we studied the effects of ß-3 type HPV49 in a novel transgenic (Tg) mouse model, using a cytokeratin K14 promoter to drive expression of the E6 and E7 genes from this virus in the basal skin epidermis and the mucosal epithelia of the digestive tract (K14 HPV49 E6/E7-Tg mice). Viral oncogene expression only marginally increased cellular proliferation in the epidermis of Tg animals, compared with wild-type littermates, and we observed no spontaneous tumor formation during their entire lifespan. However, we found that K14 HPV49 E6/E7-Tg mice were highly susceptible to upper digestive tract carcinogenesis upon initiation with 4-nitroquinoline 1-oxide (4NQO). This was a selective effect, as the same mice did not exhibit any skin lesions after chronic UV irradiation. Opposite results were observed in an analogous Tg model expressing the ß-2 HPV38 E6 and E7 oncogenes at the same anatomic sites. While these mice were highly susceptible to UV-induced skin carcinogenesis, as previously shown, they were little affected by 4NQO treatment. Overall, our findings highlight important differences in the biologic properties of certain ß-type HPV that affect their impact on carcinogenesis in an anatomic site-specific manner. Cancer Res; 76(14); 4216-25. ©2016 AACR.